The Role of Personal and Political Values in Predicting Environmental Attitudes and Pro-environmental Behavior in Kazakhstan - Agissova, Fatikha; Sautkina, Elena (Frontiers in Psychology, 2020)
Although it is widely accepted that personal values of Self-Transcendence are a positive predictor of environmentalism, and Self-Enhancement values are a negative one, these results are not conclusive for all cultural contexts. Regarding political ideologies, research concludes that liberals tend to be more concerned about the environment, than conservatives. However, this two-dimensional take on political ideologies does not grasp the diversity of political views, which could be achieved by focusing on political values. In this research, we studied the role of personal and political values in predicting environmental attitudes and behavior in Kazakhstan, a developing country in Central Asia. Using an online survey (n = 305), we found that Security was a strong predictor of both environmental concern and NEP, overshadowing the effect of traditionally accepted value dimensions of Self-Transcendence and Self-Enhancement. While Self-Direction positively predicted environmental concern, Universalism and Benevolence were positive predictors of NEP. Among political values, Civil Liberties predicted NEP positively, and had no significant effect on environmental concern, while Free Enterprise predicted environmental concern negatively, and had no significant effect on NEP. Environmental concern was a strong predictor of all pro-environmental behaviors included in the study (littering, recycling, environmental citizenship and community action), fully mediating the effect of NEP. Based on personal and political values, three profiles of Kazakhstanis who engaged differently in pro-environmental behavior, were identified.